Business law - Savage, Nigel (Butterworths, 1993)
This edition of Savage and Bradgate: Business Law critically analyses the purpose and functioning of the rules and legislation involved in common law and statute law, placing emphasis on the rationale of the law and on the economic and political context within which it operates.